Cultures Framework Model for Culture - Based Sustainable Tourism Management at Saung Angklung Udjo - Satria Akbar; Evi Novianti; Kasno Pamungkas (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Cultural tourism destinations that endure across generations are rare, and the internal cultural dynamics that sustain them remain underexplored, particularly outside the energy and mobility sectors where the Cultures Framework (Stephenson, 2023) has predominantly been applied. This study examines the cultural ensemble of Saung Angklung Udjo (SAU), a Sundanese cultural tourism destination in Bandung, Indonesia, established in 1966, to understand how its motivators, activities, and materiality are associated with sustainability outcomes. Utilizing an exploratory sequential mixed-methods design, the qualitative phase involved in-depth interviews with 17 informants across five actor groups alongside participant observation. This phase identified five motivator values, four activity categories, and four materiality components constituting SAU's cultural ensemble. These findings subsequently informed a 50-item instrument administered to 150 respondents during the quantitative phase. Pearson correlation analysis revealed that all three cultural ensemble dimensions were strongly and significantly associated with sustainability outcomes (Activities: r = .916; Motivators: r = .893; Materiality: r = .846; all p < .001), corresponding to large effect sizes. The instrument demonstrated excellent reliability (Cronbach's alpha ranging from .935 to .972). Materiality—particularly architectural and visual identity—emerged as a comparatively weaker dimension, indicating strategic avenues for targeted investment. These findings extend the application of the Cultures Framework to community-based cultural tourism within a developing-country context, demonstrating that destination sustainability is intrinsically tied to the coherence of its cultural ensemble. Practical and policy implications are discussed.